Village Community Institutions Competency Increasing Through Collaboration Programsin Flood Handling In The Central Antapani Sub-District - Mira Rosana; Ine Mariane (Universitas Serang Raya, 2024)
The problem of dirty water flooding in the Antapani Tengah Village environment is one of the environmental problems that often occurs in the city of Bandung. The dirty water flood that occurred in Antapani Tengah Village was due to dense housing, so that water absorption was decreasing because the catchment area was covered by buildings, the behavior of the community in disposing of garbage, and the lack of coordination between the community and related agencies regarding handling flood problems. The problem of flooding cannot be handled by one institution, therefore efforts should be made to find solutions to the problem through institutional collaboration. Village Community Institutions are government partners who have the duty to maintain and preserve the values ​​of life based on mutual cooperation and kinship, containing the obligations of citizens regarding harmony, security and environmental comfort. The Community Partnership Program implemented aims to help solve environmental problems, namely by providing competency improvement through collaboration programs for LKD, with the aim that LKD is able to transmit knowledge to the community so that the community has the same knowledge, knows program planning, and is able to manage collaborative governance on how to manage collaboration in dealing with environmental problems, especially in handling flood problems and waste management.